Genetic evidence of intercontinental movement of avian influenza in a migratory bird: the northern pintail (Anas acuta) - KOEHLER, ANSON V; PEARCE, JOHN M; FLINT, PAUL L; FRANSON, J. CHRISTIAN; IP, HON S (Molecular ecology, 2008)
The role of migratory birds in the movement of the highly pathogenic (HP) avian influenza H5N1 remains a subject of debate. Testing hypotheses regarding intercontinental movement of low pathogenic avian influenza (LPAI) viruses will help evaluate the potential that wild birds could carry Asian-origin strains of HP avian influenza to North America during migration. Previous North American assessments of LPAI genetic variation have found few Asian reassortment events. Here, we present results from whole-genome analyses of LPAI isolates collected in Alaska from the northern pintail (Anas acuta), a species that migrates between North America and Asia. Phylogenetic analyses confirmed the genetic divergence between Asian and North American strains of LPAI, but also suggested inter-continental virus exchange and at a higher frequency than previously documented. In 38 isolates from Alaska, nearly half (44.7%) had at least one gene segment more closely related to Asian than to North American strains of LPAI. Additionally, sequences of several Asian LPAI isolates from GenBank clustered more closely with North American northern pintail isolates than with other Asian origin viruses. Our data support the role of wild birds in the intercontinental transfer of influenza viruses, and reveal a higher degree of transfer in Alaska than elsewhere in North America.